The process of fractioning of the liquids of the natural gas of Camisea and its impact on the economy of the refining of hydro carbonates in Perú - Santillana, Jaime (2003)
It is shown the design of a fractionation plant of natural gas liquids for Camisea Project. It is described the general characteristics of streams and process equipmentsfor the plant. The economic feasibility of the proposed design is analysed and it is carried out an evaluation of impact of the liquid products of Camisea Project in the hydrocarbons refining economy in Peru.